UAV Photogrammetry and 3D Modelling of Complex Architecture for Maintenance Purposes: the Case Study of the Masonry Bridge on the Sele River, Italy - Pepe, Massimiliano; Costantino, Domenica (Periodica polytechnica. Civil engineering. Bauingenieurwesen, 2021)
The aim of this paper is to identify a suitable methodology to realize, in an easy and quick way, 3D models of complex structures. To achieve this aim, the first step is to build the 3D model of the scene under investigation using photogrammetric modelling. This task was carried out by the use of algorithms based on Structure from Motion (SfM) - Multi View Stereo (MVS) approaches and using camera-generated images supplied in the UAS (Unmanned Aerial system). Once built the 3D point cloud of the structure under investigation, the geometry of each element was reconstructed with 3D profile reconstruction using Rhinoceros software and a few plug-ins developed in this software. Indeed, this paper shows, through a case study of a masonry bridge of special architectural and historic value built in the middle of 1800s and located in the south of Italy, the potential of the method developed in order to manage a maintenance or restoration project.